ISOLATION, IDENTIFICATION AND SELECTION OF LACTIC ACID BACTERIA CULTURES FOR CHEESEMAKING - Soda, Morsi El; Ahmed, N.; Omran, N.; Osman, G.; Morsi, A. (Emirates Journal of Food and Agriculture, 2017)
Lactic Acid Bacteria (LAB), which are considered to be the most useful microorganisms to society, are involved in the manufacture of thousands of fermented foods. They are also beneficial in flavoring foods, inhibiting pathogenic as well as spoilage bacteria in these products. A total of 2000 isolates of LAB were obtained from traditional Egyptian dairy products (different types of raw milk, ras, domiatti and kareish cheese, mish, cream, butter and fermented milk such as laban, rayeb and zabady) obtained from different regions in Egypt. The pre-identification tests were performed according to the morphological characteristics: catalase test, growth at 10°C and 45°C, growth in the presence of 6.5% NaCl and Co2 production. The isolates were subjected to phenotypic and cell wall protein characterization analyses. Phenotypically, 1006 strains were identified using API 50 CHL and API 20 Strep (Apparatus and procedure of identification). The SDS-PAGE technique (Sodium dodycyl sulfate) of whole cell protein was evaluated as an advanced tool for the identification of LAB. Therefore protein fingerprints were registered for 514 strains and compared to a large number of LAB reference strains stored in database format. The SDS-PAGE technique confirmed 94% of the API identification results. The identified strains were tested for acidifying activity, autolytic and aminopeptidase properties, antagonistic activities and polysaccharides production. Selected cultures where then evaluated as starter or adjunct cultures for Ras and Domiatti cheese production in the cheese research laboratory. Higher cheese flavor scores were consistently obtained in Ras cheese made with cultures showing high peptidase and esterase activity and a high rate of autolysis. Development of free amino acids and free fatty acids in Ras cheese were always higher when compared to the cheese made using other starters.